How the communication between designers was affected by ActionSketch, a technique to improve sketches in interaction design - Barros, Gil; Veloso, Leandro (InfoDesign, 2013)
Sketching is a well-established practice in many areas of design. Sketches and communication are tightly connected because one of the main functions of sketches is to help a designer communicate with colleagues. Interaction design is a new field of design that poses challenges for sketching and considering these challenges we proposed ActionSketch, a technique to improve the process of sketching for interaction design. We conducted four workshops with 24 professionals, followed by a period of continued use of approximately three weeks and an individual interview. Regarding communication between professionals, we found two sets of results: when all designers knew the technique and when some or all of the designers didn’t know it. In the first case the technique facilitated the communication and points to three main benefits: verbal explanation was no longer needed; drawings became more evident; presentation of the drawings was less important. In the opposite case it ended being an obstacle. We argue that this is an intrinsic dilemma for the technique, there is a learning barrier, and we can only make the process easier. However, when at least one designer knew the technique it was no longer a barrier and even became a facilitator in critic situations. Given these results, claim that the technique has a positive effect on communication between professionals.